Seleksi Generasi M2 yang Berumur Genjah Hasil Iradiasi Beberapa Kultivar Padi Lokal Sumatera Barat - Putri Rizki Utami; Zulfadly Syarif; Irfan Suliansyah (Program Studi Agroteknologi Fakultas Pertanian Universitas Andalas, 2018)
The purpose of this study is to obtain a early-harvest rice mutant maturity, ideal height, number of tillers, and ideal height. The method was used in this study is the method of pedigree. Planting M2 was the first stage of selection to be carried out next by pedigree. Prospective mutants in M2 generation of irradiated cultivars of sijunjuang consist of; a) 2 genotypes of very mature candidate mutants (104 hss), b) 152 genotypes of maturing mutant candidates (110 hss - 120 hss), c) 18 genotypes of prospective mutants mature and have ideal high criteria, and d) 2 genotypes of mating candidates that are mature and have the ideal total number of tillers; e) 7 genotypes of prospective mutants with weight of dry harvest grain above average yield per hectare from the description of kutivar Sijunjuang ie 5.5 Tons/Ha. Mutant candidates in M2 generation resulting from irradiation Kuriak Kusuik consist of; a) 2 genotypes of very early genetic candidates (104 hss), b) 76 genotypes of mature candidates (113 hss -124 hss), c) 323 genotypes of moderate mutant candidates (126 hss -147 hss), d ) 123 genotypes of prospective mutants very mature and have ideal high criteria and e) 4 genotypes of prospective mutants mature with high and total number of ideal tillers, f) as many as 18 genotypes of prospective mutants who have weight of dry grain harvest above the average production per hectare of Kuriak Kusuik cultivar description and g) has one genotype of prospective mutants that have a early-harvest age and have an ideal agronomic character.